Symbolic mapping and allocation for the Cholesky factorization on NUMA machines: Results and optimizations. (August 2013) - Jeannot, Emmanuel
We discuss some performance issues of the tiled Cholesky factorization on non-uniform memory access-time (NUMA) shared memory machines. We show how to optimize thread and data placement in order to improve performance. The final result is 50% faster than PLASMA and 75% faster than MKL.